2020
DOI: 10.1038/s41598-020-61352-0
|View full text |Cite
|
Sign up to set email alerts
|

NBEAL1 controls SREBP2 processing and cholesterol metabolism and is a susceptibility locus for coronary artery disease

Abstract: Dysregulated cholesterol homeostasis promotes the pathology of atherosclerosis, myocardial infarction and strokes. Cellular cholesterol is mainly regulated at the transcriptional level by SREBP2, but also through uptake of extracellular cholesterol from low density lipoproteins (LDL) via expression of LDL receptors (LDLR) at the cell surface. Identification of the mechanisms involved in regulation of these processes are thus key to understand the pathology of coronary artery disease. Here, we identify the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…NBEAL1 was known as a susceptibility locus of CAD, which was highly expressed in the heart and artery [ 41 ]. It affected cholesterol metabolism and LDL uptake by regulating the activity of SREBP2 in cells and then affected the pathogenesis of CAD afterwards [ 42 ]. However, FGD6 might be a novel CAD susceptibility locus, which regulated the proangiogenic activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…NBEAL1 was known as a susceptibility locus of CAD, which was highly expressed in the heart and artery [ 41 ]. It affected cholesterol metabolism and LDL uptake by regulating the activity of SREBP2 in cells and then affected the pathogenesis of CAD afterwards [ 42 ]. However, FGD6 might be a novel CAD susceptibility locus, which regulated the proangiogenic activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Gene FES, which encodes the human cellular counterpart of a feline sarcoma retrovirus protein with transforming capabilities, is well known to be associated with myeloid leukemia (99), but recent studies observed the function of FES in modulating atherosclerotic plaque vulnerability (100) and the effect of tobacco smoking on DNA methylation of FES (75). Genes ICA1L and NBEAL1 were mapped by the same locus (index SNP: rs114123510), and both are related to cholesterol metabolism, in which dysregulation promotes the pathology of atherosclerosis, MI, and strokes (101). Notably, C2orf69-Brain Caudate basal ganglia gene-trait pair was the only one observed overlapping gene-tissue pair between smoking status and HF.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, our results also reveal that cholesterol uptake is highly induced in γ‐secretase‐deficient cells in which C99 levels are increased. The intriguing failure of a negative feedback mechanism to downregulate C99‐mediated cholesterol import suggests that the continuous uptake of cholesterol might occur through one of the SREBP2‐independent cholesterol receptors expressed in the cell (Makar et al , ; Bindesboll et al , ).…”
Section: Discussionmentioning
confidence: 99%